2007
DOI: 10.1111/j.1741-6787.2007.00096.x
|View full text |Cite
|
Sign up to set email alerts
|

Incontinence: Assessment, Diagnosis, and Management in Two Rehabilitation Units for Older People

Abstract: Because incontinence remains an issue for older people and the clinical implications of sustained incontinence are multifaceted, strategies should focus on the development of practice towards evidence-based multidisciplinary approaches to continence promotion and management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 46 publications
(78 reference statements)
2
25
0
Order By: Relevance
“…This study of an 80% female population reported an inadequacy of assessment, suboptimal management and an over-reliance on containment as a sole source of management of the problem. These findings have been replicated in Ireland [17]. Figure 2 shows the documented treatment for urinary incontinence in communitydwelling older people from the audit.…”
Section: Lower Urinary Tract Symptoms In Older Womensupporting
confidence: 50%
“…This study of an 80% female population reported an inadequacy of assessment, suboptimal management and an over-reliance on containment as a sole source of management of the problem. These findings have been replicated in Ireland [17]. Figure 2 shows the documented treatment for urinary incontinence in communitydwelling older people from the audit.…”
Section: Lower Urinary Tract Symptoms In Older Womensupporting
confidence: 50%
“…For this reason research was undertaken to investigate the context within which incontinence was managed in a rehabilitation unit in Ireland. This was part of a larger funded study (Coffey et al. , 2007, Wright et al.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Older people with urinary incontinence may look to healthcare professionals for someone to talk to and receive individualized, person centred care. They are looking for choices on how to manage their condition and symptoms and many expect active participation in their care programme and decision‐making process (Coffey et al. , 2007; Kincade et al.…”
Section: Patient Perspectivementioning
confidence: 99%
“…, 2008). Equally, quality of life can be markedly affected by the failure to treat and adequately manage urinary incontinence with physical, social, psychological and financial consequences (Coffey et al. , 2007; Jamison et al.…”
Section: Patient Perspectivementioning
confidence: 99%
See 1 more Smart Citation